URGENSI PENDIDIKAN MELEK MEDIA (MEDIA LITERACY) BAGI ANAK - Fadlilah, Sayyidatul (Tarbiyah, 2014)
Media has an important role in human life.Â  Beside it becomes source of the information and knowledge, it can also become an entertainment source for adults and kids. The wrong usage of media can cause problems for the nationâs life. This paper is written based on the writerâs experience in joining ToT (Training of Trainers) on media literacy and media watch, facilitating media literacy and media watch program, and becoming one of the researchers and enumerators of media watch towards two newspapers by using content analysis; the project ofÂ  Strengthening Womanâs Rights (SWR) cooperated with Indonesian Government represented by PSGA (the Center of Gender and Children Study) ofÂ  IAIN Walisongo Semarang and Germany Government (GTZ). From the output of those activities, the writer recommends to all parties to be care of the usage of media by children. Children need smartness in accessing, enjoying, interpreting, using, and analyzing media. In other words, media literacy education becomes urgent and significant to be educated and implanted by their parents, society, and even schools towards the children. Whereas, industry of media must be wise in producing and providing information for the society, and obey the rules established by UU Penyiaran, P3 (Pedoman Perilaku Penyiaran) and SPS (Standar Program Siaran), and the rules made by Dewan Pers and UU Perlindungan Anak.Key words: Media, Media Literacy Education, Moral, Children